Ultaco Game Development as a Media to Introduce Covid-19 Health Protocol in Early Childhood - M. Fadlillah; Rendy Setyowahyudi (AL-ISHLAH: Jurnal Pendidikan, 2021)
The most effective way to prevent the spread of Covid-19 is to comply with health protocols. However, this habit is still tricky for some Indonesians, including in early childhood. This study aimed to develop and test the Ultaco game's quality as a medium in introducing the Covid-19 health protocol to early childhood. The research and development (RD) method was used in this study. In developing the Ultaco game, three steps carried out, including planning, design, and development. Product quality testing was carried out using three techniques: alpha test, beta test, and final evaluation. This study showed that the Ultaco game is a kind of snakes and ladders game that contains the Covid-19 health protocol, including wearing a mask, maintaining distance, staying at home, washing hands, covering sneezes, exercising diligently, and eating nutritiously. The trial results showed that the Ultaco game is of good quality and is suitable for use as a medium for introducing the Covid-19 health protocol to early childhood. This is based on the average score of the alpha test score of 4.48, the beta test score of 3.41, and the final evaluation score of 3.64. This study implies that children can become accustomed to complying with the Covid-19 health protocol with attractive, fun, and fun game media.